1989
DOI: 10.1159/000261208
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Rat Fissure Caries by Sodium Fluoride Varnish (Duraphat®) with Different Fluoride Concentrations

Abstract: 125 Osborne-Mendel rats were weaned at 22–23 days, inoculated with Streptococcus sobrinus and fed a cariogenic diet for 40 days. The control group received no treatment; the study groups received applications of Duraphat® containing 2.3, 1.1, or 0.6% fluoride or a placebo varnish on days 21–23. The placebo varnish had no effect on caries. Fissure caries was significantly reduced by the 2.3 and 1.1% fluoride varnishes, whereas the caries reduction found after treatment with the 0.6% fluoride varnish was not sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The costs of applying the varnish more or less often were assessed in a sensitivity analysis. While a dose‐response gradient between fluoride concentration and effect seems likely, there were insufficient data for determining exactly whether a different application frequency was also associated with different effectiveness. We thus assumed that the effectiveness did not differ by application frequency.…”
Section: Methodsmentioning
confidence: 99%
“…The costs of applying the varnish more or less often were assessed in a sensitivity analysis. While a dose‐response gradient between fluoride concentration and effect seems likely, there were insufficient data for determining exactly whether a different application frequency was also associated with different effectiveness. We thus assumed that the effectiveness did not differ by application frequency.…”
Section: Methodsmentioning
confidence: 99%
“…However there have been no studies reported examining the anticaries efficacy of low-fluoride professional preparations on preschool children, and reports have been confined to animal stud ies. No significant reduction in caries efficacy has been found in rats [Hefti, 1982: Seppa et al, 1989], Hagan and Bawden [1985] have presented data of a clinical study in which full-and half-strength APF operator-applied treat ments were evaluated, but this work was conducted on older children (11-to 15-year-olds).…”
mentioning
confidence: 99%